Effects of colored lights on an individual's affective impressions in the observation process - Xie, Xing; Cai, Jun; Fang, Hai; Tang, Xiaoying; Yamanaka, Toshimasa (Frontiers in Psychology, 2022)
The lighting environment has an important influence on the psychological and physical aspects of a person. On certain occasions, reasonable lighting design can regulate people's emotions and improve their feelings of comfort in a space. Besides, specific lighting can create a specific atmosphere according to space requirements. However, in the study of an individual's affective impressions, there is still some uncertainty about how colored lights affect an individual's moods and impressions toward visual objects. This research improves the understanding of the emotional impact of colored light in space. To better understand the lighting environment in the observation process, the project studied the effects of four groups of lights (green, blue, red, and yellow) on the participants' moods and impressions. Participants watched two sets of visual images under four different lighting conditions and provided feedback on their emotions and evaluations through the Multiple Mood States Scale, Two-Dimensional Mood Scale, and Semantic Differential Scale. The results show that different colors of light have a significant effect on mood, and red light can arouse emotional changes to calm, irritated, relaxed, nervous, stability, and pleasure. At the same time, different colors of light have a certain relevance to participants' impressions and this provides further research value for the design of the colored light environment in an individual's affective impressions. Therefore, this study discusses the feasibility of colored lights as a display method, which has potential application prospects for constructing different space atmospheres.